Blended Learning Analysis for Sports Schools in Indonesia - Adi, Sapto; Fathoni, Abi Fajar (International Journal of Interactive Mobile Technologies (iJIM), 2020)
The students at Sports School are athletes that often leave school for training camps or participate in competitions outside the city. This study therefore, aims to determine the characteristics, conditions, and needs of Sports Schools in Indonesia as a basis for the Blended Learning development. Data were collected on information related to Sports School in various regions of Indonesia, through surveys. The result showed that there are special services for students that participate in training camps and competitions. However, their skill is ineffective and requires an increase in teaching hours and workload. Therefore, based on the characteristics of the Sports School and the needs of teachers and students, the Blended Learning model was developed